QUANTUM SIMULATION OF WEAKLY-BOUND COMPLEXES USING DIRECT AB-INITIO ENERGY POINTS - Gregory, J; Clary, D (1995)
We describe the use of a quantum diffusion Monte Carlo algorithm coupled directly to an ab initio program which supplies the (MP2) electronic energy for the quantum simulation. This method does not require a fit to a multidimensional potential energy surface. We demonstrate the application of this method to (HF)2 for which we have calculated the fully anharmonic zero-point energy, the ground state rotational constants, ro-vibrational wavefunctions and the tunnelling splitting. The method we describe is computationally demanding, but general, and will be particularly attractive for use on parallel computers. © 1995.